Catalytic behavior of copper oxide and ceria based catalysts for the co preferential oxidation reaction - Mariño, Fernando J.; Baronetti, Graciela T.; Bergamini, María L.; Moreno, Máximo; Schönbrod, Betina; Laborde, Miguel A. (Revista Ciências Exatas, 2009)
CO preferential oxidation on CuO and CeO2 catalysts is studied. Catalysts were prepared by two different methods: coprecipitation of both cations and copper impregnation on ceria previously obtained. The influence of several operation variables (reaction temperature, residence time, concentrations) on the activity and selectivity of the catalytic samples is analysed. In addition, a kinetic study of the CO oxidation reaction is performed. Two different kinetic expressions are compared: a power-law type expression and a Mars-van Krevelen expression. In the first case, CO and O2 reaction orders are fitted. In the second case, the parameters adjusted for both reaction steps (a reduction step and an oxidation one) stated by the model are: the preexponential factors of the kinetic constants (k0 O2 y k0 CO), the corresponding activation energies (EaO2, EaCO) and the O2 reaction order in the oxidation step (n).